Mechanical properties and dislocation nucleation in nanocrystals with blunt edges. (5th December 2017) - Amodeo, Jonathan; Lizoul, Khalid
Abstract: The deformation of blunt nanocrystals under uniaxial compression is modelled using molecular dynamics simulations. Ni3 Al blunt nanoparticles are built using a simple algorithm that allows continuous shape design from perfectly-sharp nanocubes to nanospheres including a large set of cuboid shapes. Simulation results show that blunt nanoparticles are significantly stronger in comparison to their perfectly cubic counterparts and deform due to the nucleation of partial dislocations and deformation twins. Furthermore, while the early plastic deformation of nano-objects is generally attributed to the nucleation of dislocations from the surface, here we show that homogeneous dislocation nucleation may also happen in blunt nanoparticles and a size-dependent transition parameter is defined. This study emphasizes how much the design of virtual samples is crucial when modeling nano-objects mechanical properties using molecular dynamics simulations and provides new insights onto potential incipient plasticity features at the nanoscale. Graphical abstract: Highlights: Nanoparticles with blunt edges are investigated under compression using molecular dynamics simulations. Samples are designed using a single blunting parameter α . Smoothing nanoparticles edges and corners decreases the force response but increases the compressive stress response. Surface and homogeneous dislocation nucleation occur depending on α and size.